Strategic Mapping of Corporate and Business Strategies in the Healthcare Sector: A Case Study of ABC Hospital in Indonesia - Muhammad Iqbal Alamsyah; Puspo Dewi Dirgantari; Agus Rahayu; Lili Adi Wibowo; Disman (East Asian Journal of Multidisciplinary Research, 2023)
Advancements in medical technology, such as the implementation of electronic medical record systems and the adoption of telemedicine, have revolutionized the provision of healthcare services. This study aimed to formulate a suitable strategy for the company to foster growth and maintain its market position. The research employed a qualitative approach. Based on the findings, a growth strategy is strongly recommended for ABC Hospital. Given the rising demand for healthcare services and the imperative to deliver optimal care to the community, ABC Hospital should prioritize expanding its operations, acquiring established facilities, and investing in resources and capabilities to meet the needs of the growing population. Implementing a growth strategy will enable ABC Hospital to capitalize on market opportunities, strengthen its competitive position, and ensure long-term viability in providing exceptional healthcare.